2022
DOI: 10.3390/biom12060801
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Silk Sericin for Diabetic Wounds: An In Situ-Forming Hydrogel to Protect against Oxidative Stress and Improve Tissue Healing and Regeneration

Abstract: Chronic wounds are one of the most frequent complications that are associated with diabetes mellitus. The overproduction of reactive oxygen species (ROS) is a key factor in the delayed healing of a chronic wound. In the present work, we develop a novel in situ-forming silk sericin-based hydrogel (SSH) that is produced by a simple methodology using horseradish peroxidase (HRP) crosslinking as an advanced dressing for wound healing. The antioxidant and angiogenic effects were assessed in vitro and in vivo after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…As previously stated, the silk of silkworms has multiple potential applications in biomedicine due to its good biocompatibility, mechanical properties, degradability, and plasticity. Several studies have shown that silk-based material dressings are more successful than traditional ones in the healing of skin wounds [ 34 , 159 , 160 , 161 ]. For instance, Batista-Silva et al [ 159 ] developed a novel in situ-forming SS hydrogel as an enhanced dressing for wound healing using a simple technology based on horseradish peroxidase crosslinking ( Figure 7 A).…”
Section: Particulate Drug Delivery Systems In Wound and Skin Regenera...mentioning
confidence: 99%
See 2 more Smart Citations
“…As previously stated, the silk of silkworms has multiple potential applications in biomedicine due to its good biocompatibility, mechanical properties, degradability, and plasticity. Several studies have shown that silk-based material dressings are more successful than traditional ones in the healing of skin wounds [ 34 , 159 , 160 , 161 ]. For instance, Batista-Silva et al [ 159 ] developed a novel in situ-forming SS hydrogel as an enhanced dressing for wound healing using a simple technology based on horseradish peroxidase crosslinking ( Figure 7 A).…”
Section: Particulate Drug Delivery Systems In Wound and Skin Regenera...mentioning
confidence: 99%
“…Several studies have shown that silk-based material dressings are more successful than traditional ones in the healing of skin wounds [ 34 , 159 , 160 , 161 ]. For instance, Batista-Silva et al [ 159 ] developed a novel in situ-forming SS hydrogel as an enhanced dressing for wound healing using a simple technology based on horseradish peroxidase crosslinking ( Figure 7 A). The authors observed that the SS-hydrogels promoted wound closure and a decrease in granulation tissue compared to commercial Tegaderm TM dressing ( Figure 7 B).…”
Section: Particulate Drug Delivery Systems In Wound and Skin Regenera...mentioning
confidence: 99%
See 1 more Smart Citation
“…Silk sericin is a globular protein with remarkable biodegradability, biocompatibility, antioxidant capacity, and regenerative abilities, including faster wound healing abilities, accelerated cell proliferation, and a low inflammatory profile. Silk sericin is less explored than silk fibroin; however, fiber-based scaffolding systems for DFU care have already been engineered [ 59 , 63 ]. Indeed, Gilotra et al demonstrated the antioxidant potential of silk sericin without compromising cell viability and verified its ability to accelerate wound healing without triggering any inflammatory response [ 64 ].…”
Section: Immunomodulatory Agentsmentioning
confidence: 99%
“…Studies have shown that curcumin can inhibit EMT to reverse renal brosis progression [8], can effectively inhibit EMT via the TGF-β1 and Smad pathways [9] and may be used as an effective agent in additional treatments for RIF. Sericin is a complicated polypeptide that is extracted from home silkworm cocoons; agricultural scientists have reported that it has good biocompatibility and that its immunogenicity is negligible [10].…”
Section: Introductionmentioning
confidence: 99%